INTEGRATION OF SOCIAL CARE CHARACTERS AND MORAL INTEGRATIF ON SOCIAL SCIENCE LESSONS IN ELEMENTARY SCHOOL - Hasnah Kanji; Nursalam Nursalam; Muhammad Nawir; Suardi Suardi (AL-ISHLAH: Jurnal Pendidikan, 2020)
The purpose of this study was to find an integrative model of social care character in social science subjects in elementary schools using integrative moral knowledge, moral feelings, moral sinverbals, moral action, moral habitus and moral culture. The reality that happens is that students experience moral degradation so that they need the integration of character education in the learning process. The formulation of the research problem is how to model the integration of national character education in social science learning. The research method used qualitative methods with 10 informants consisting of the principal, teachers, students, parents. The data technique used interview, observation and documentation instruments, then the data were analyzed through data reduction, data display and verification. The paradigm used in the research is the moral education paradigm. The results of the research model of the integration of social caring character education consist of six moral levels, namely moral knowledge, moral feelings, moral synergy, moral action, moral habits and moral culture which are integrated with the values of social caring character in the learning process of social science.